Features of organization and maintenance of physical education of students of higher pedagogical educational establishments - A.N. Kolumbet (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
A purpose of work is an analysis of data of modern scientific literature for organizations and maintenances of physical education of students of higher educational establishments. An analysis over of 273 publications of domestic and foreign scientists and researchers is brought. Estimation over of positions of conception of development of students' physical internals, co-ordination and co-ordinating capabilities are brought on employments on physical education. Data of modern scientific literature are considered on development and perfection of motive internals and co-ordinating capabilities of modern youth. The problems of health of modern young man level are shown. It is well-proven that the professional capabilities of modern teacher are straight related to good physical preparedness. The further ways of development of motive capabilities of young people are certain. Finding allows establishing that is now accumulated there is enough material which allows stepping over through the traditional aspects of pedagogical process of mastering the man of motive abilities and skills. Untraditional ways are shown to the process of physical education of students of pedagogical higher educational establishments.